2022
DOI: 10.21203/rs.3.rs-1557881/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplementation of trisodium citrate improves recovery rate of subclinical mastitis in crossbred cows

Abstract: Mastitis is the top most reason for antibiotic usage, which is an important public health concern due to antimicrobial resistance development in pathogen. Citrate is an important precursor for milk synthesis and regulation of homeostasis between Ca2+ and H+ ions and thereby milk fluidity. The aim of this study was to evaluate the effect of trisodium citrate (TSC) on recovery of subclinical mastitis (SCM) in HF crossbred cows. Apparently healthy lactating cow’s milk samples were screened by somatic cell count (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Shaikh et al (2019) observed that administration of TSC powder (30 mg/kg, BID for five days) was found to be more efficacious for prevention of SCM in cows maintained under conventional housing system than in loose housing system. Recently, we reported that supplementations of TSC alone cause no significant changes in milk yield and its composition, but reduced milk SCC and CMT score with more bacteriological cure rate in SCM affected cows (Sahu et al, 2022).…”
Section: Effect Of Trisodium Citrate On Mastitis Affected Dairy Animalsmentioning
confidence: 95%
“…Shaikh et al (2019) observed that administration of TSC powder (30 mg/kg, BID for five days) was found to be more efficacious for prevention of SCM in cows maintained under conventional housing system than in loose housing system. Recently, we reported that supplementations of TSC alone cause no significant changes in milk yield and its composition, but reduced milk SCC and CMT score with more bacteriological cure rate in SCM affected cows (Sahu et al, 2022).…”
Section: Effect Of Trisodium Citrate On Mastitis Affected Dairy Animalsmentioning
confidence: 95%
“…To meet these demands, dairy processors now require milk that adheres to stringent international standards, with Bulk Milk Somatic Cell Count (BMSCC) and Total Bacterial Count (BMTBC) serving as key benchmarks [6,46]. However, mastitis, a prevalent ailment among dairy cows, remains a significant and costly challenge for the dairy industry [51,50]. Mastitis, characterized by inflammation of the mammary glands, threatens both animal welfare and the financial stability of dairy operations [29].…”
Section: Introductionmentioning
confidence: 99%